UroVysion Fluorescence in situ hybridization (UroVysion FISH) assay for detecting Turkish bladder cancer patients in voided urine: A preliminary study - Dodurga, Yavuz; Avcı, ÇIğır Biray; Yılmaz, Sunde; NazIı, Oktay; Çoğulu, Özgür; Cankaya, Tufan; Gündüz, Cumhur (Contemporary Oncology/Współczesna Onkologia, 2013)
Bladder cancer is the fourth most common cancer in men and the fifth most common cancer worldwide. UroVysion FISH has high sensitivity and specificity for urothelial carcinoma detection. We investigated the genetic marker detected by the UroVysion FISH technique in diagnosis of Turkish bladder cancer patients and compared these results with the urine cytology and cystoscopy. Urine specimens were analyzed using UroVysion FISH probes for abnormalities in centromeric chromosomes 3, 7, and 17 and locus-specific 9p21. Morning fresh voided urine samples were collected from each patient for FISH analysis. Cytology and histopathology analysis were performed by the pathology department. Twenty-seven bladder cancer patients (23 male and 4 female) with a history of bladder cancer who provided informed consent were included in this prospective study. The results showed that cancer was detected in 8 patients via FISH; 7 via cytology; 12 via cystoscopy. According to the pathology results, 15 were normal, 10 high-grade carcinoma and 2 low-grade carcinoma. Sensitivity of these methods with FISH, cytology, and cystoscopy was 29.6%, 25.9%, and 44.4%, respectively. In conclusion, all tests have different advantages and disadvantages. Also, larger studies will be needed to confirm these results. But, UroVysion FISH appeared to have good specificity for detecting bladder cancer in urine specimens and also it is important to correlate the FISH results with the cystoscopy and cytological findings.